Pemanfaatan Bank Sampah untuk Meningkatkan Kesadaran Lingkungan di Kelurahan Gunung Panjang, Samarinda Seberang - Astati, Andi Sitti; Suriaty, Andi Sitti Asti; Sukma, Adji Ananta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Waste management issues in Indonesia’s rapidly urbanizing areas have driven the emergence of community-based initiatives such as waste banks. This study examines the role of Pinang Lestari Waste Bank, located in Gunung Panjang Subdistrict, Samarinda Seberang, in reducing landfill-bound waste and empowering the local economy. Using a mixed-methods approach, data were collected through interviews with managers and residents, alongside quantitative records of waste volumes and recycled products. The findings show a monthly waste reduction of approximately 7 tons and annual revenue of around IDR 40,000,000 from compost, eco-enzymes, and plastic-glass crafts. Community participation in waste sorting increased, reflecting the effective application of circular economy principles. These results offer a foundation for replicating this waste bank model in other regions as a sustainable waste management strategy